PENGEMBANGAN MEDIA VISUAL BERBASIS MIND MAPPING PADA PEMBELAJARAN TEMATIK SISWA KELAS V MI DARUSSALAM - Aprilia, Cahya; Sofiarini, Andriana; Aswarliansyah (LP3MKIL, 2022)
This study aims to determine the design of developing mind mapping-based visual media in the thematic learning of fifth grade students of MI Darussalam and to produce valid, practical and effective mind mapping-based visual media. The type of research is Research and Development with the ADDIE development model. The subjects of this research were the fifth grade students of MI Darussalam Lubuklinggau. Data collection techniques used are observation, interviews, questionnaires, documentation and tests. Based on the results of the assessment analysis by the three experts, namely: linguists, material experts and media experts, it showed that mind mapping-based visual media met the valid criteria with an average score of 0.88. Meanwhile, from the analysis results of the teacher and student practicality assessment sheets, it was found that the engklek game met the practical criteria with an average score of 97%. In the field test, an N-gain (g) of 0.73 was obtained with a high classification, which means that mind mapping-based visual media has a high level of effectiveness. Based on the results of the study, it can be concluded that mind mapping-based visual media is proven to be valid, practical and effective in learning theme 1 for class V Elementary School